2019
DOI: 10.29244/jitkt.v11i1.21971
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distributions of Nutrients and Chlorophyll-A: a Possible Occurrence of Phosphorus as a Eutrophication Determinant of the Jakarta Bay

Abstract: Phytoplankton blooms due to nutrient enrichment (eutrophication) have been considered as the primary factor causing several massive fish kills occurred in the Jakarta Bay. This study aims to determine the spatial variation of phytoplankton abundance based on chlorophyll-a concentration and its relationship with nutrient level and composition. A field observation was conducted in July 2015 measuring chlorophyll-a and nutrient concentrations. Chlorophyll-a was measured using fluorometer Trilogy AU-10 while nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
1
5
0
9
Order By: Relevance
“…Sharker et al found similar results to the recent study, where phosphate and nitrate have a significantly positive correlation with chlorophyll-a in the Bay of Bengal [59]. Prayitno and Afdal also revealed similar results in observations conducted in Western Jakarta Bay, and the chlorophyll-a was found to have a positive and significant correlation with phosphate (r = 0.803, P<0.05) and nitrate (r = 0.673, P<0.05) [60]. Nitrate is one of the N (nitrogen) nutrients phytoplankton needs for growth.…”
Section: Resultssupporting
confidence: 74%
“…Sharker et al found similar results to the recent study, where phosphate and nitrate have a significantly positive correlation with chlorophyll-a in the Bay of Bengal [59]. Prayitno and Afdal also revealed similar results in observations conducted in Western Jakarta Bay, and the chlorophyll-a was found to have a positive and significant correlation with phosphate (r = 0.803, P<0.05) and nitrate (r = 0.673, P<0.05) [60]. Nitrate is one of the N (nitrogen) nutrients phytoplankton needs for growth.…”
Section: Resultssupporting
confidence: 74%
“…Menurut (Prayitno & Afdal, 2019) kelarutan CO 2 bebas dalam air laut ini dimanfaatkan untuk aktifitas proses fotosintesis oleh makhluk hidup perairan. Biomassa dalam ekosistem lamun dapat berperan sebagai penyimpan karbon dioksida dari atmosfer.…”
Section: Parameter Kualitas Perairanunclassified
“…Konsentrasi klorofil-a di perairan pantai Maroon sebesar 1,09 mg/m 3 (Prihatin et al, 2018) dan muara Sungai Serang dengan rata-rata sebesar 1,76 mg/m 3 (Maslukah et al, 2017) setara dengan 1,09 μg/L dan 1,76 μg/L. Pada perairan muara Sungai Angke diperoleh konsentrasi klorofil-a dengan ratarata sebesar 3,19 μg/L (Prayitno & Afdal, 2019). Pada perairan muara sungai Tallo, Maros, dan Pangkep konsentrasi Klorofil-a secara berturut-turut dengan rata-rata sebesar 4,52 μg/L, 1,40 μg/L, 2,72 μg/L (Lukman et al, 2014).…”
Section: Perbedaanunclassified
“…Fenomena ini di sebagian besar perairan dunia meningkat frekuensi, intensitas dan distribusi geografis selama beberapa dekade terakhir (Blondeau-Patissier, et al, 2014) termasuk di perairan Indonesia. Pada beberapa perairan di Indonesia seperti Teluk Jakarta (Prayitno & Afdal, 2019) dan pesisir Sulawesi Selatan (Lukman et al, 2014) konsentrasi klorofil-a menunjukkan peningkatan.…”
unclassified